Examining the Feasibility and Acceptability of a Telehealth Behaviour Change Intervention for Rural-Living Young Adult Cancer Survivors - Price, Jenson (Université d'Ottawa / University of Ottawa, 2019)
Regular physical activity (PA) participation and fruit and vegetable (FV) consumption confers numerous positive health outcomes for cancer survivors, including prevention of cancer recurrence, second primary cancers, and other non-communicable chronic diseases. Rural-living young adult cancer survivors (YAs) possess unique barriers and concerns that influence their ability to participate in traditional face-to-face behaviour change interventions. Few researchers have explored alternative means for delivering behaviour change interventions grounded in theory utilizing a mixed-methods approach to assess processes of change and behavioural outcomes. To fill this gap and provide recommendations for future interventions and services focused on positive health behaviours in this population, the objective of the research presented in this thesis was to explore the feasibility and acceptability of a 12-week theory-based telehealth behaviour change intervention aiming to improve PA and FV consumption using a single-arm, mixed methods pilot trial. Over a 7-month period, 14 YAs self-referred. Of these 14, 5 were eligible and consented to participate with 3 completing the study. Retention to the study was 73% and adherence to the health coaching program ranged from 66.67-100% with a 40% attrition rate. Inquiry into the acceptability of the intervention offered insight into participants experiences, which was summarized within five themes: (1) the more time the better, (2) the human factor, (3) supporting access, (4) influencing the basic psychological needs, and (5) finding motivation. Collectively, the findings suggest the methods used require minor modifications before being deemed feasible despite the general acceptability of the intervention. Importantly, they highlight the necessity of more expansive recruitment strategies and a need to explore participants’ underlying intentions for participating in behaviour change interventions. Further, recommendations are made based on the findings to improve this style of intervention, including testing stepped down models of support because it may help some YAs maintain behaviour change post-intervention.
Keywords: Telehealth; Health behaviour change; Self-determination theory; Mixed methods; Rural; Young adults; Cancer